Production, Radiolabeling and Biodistribution Studies of 175Yb-DOTMP as Bone Pain Palliation: 175Yb-DOTMP as bone pain palliation - Laleh Safarzadeh; Mohammad Ghannadi-Maragheh; Ali Bahrami-Samani; Akbar Anvari; Seyed Mahmoud Reza Aghamiri; Simindokht Shirvani-Arani (Iranian Journal of Pharmaceutical Sciences, 2012)
Bone is the third most common site of metastatic disease. Bone pain is the major source of morbidity associated bone metastasis. Bone-seeking radiopharmaceuticals have been applied for many years. The ability to simultaneously treat multiple sites of disease with a more probable therapeutic effect in earlier phases of metastatic disease is one of the advantages of radiopharmaceuticals. 175Yb is one of the radioisotopes with suitable properties for developing various nuclear medicine agents. Some of these proper properties include 4.2 days half-life, gamma-rays emitted, radionuclidic purity. Radiopharmaceuticals capable of targeting bone tumors generally use phosphonic acid functionality as the targeting moiety. In this direction cyclic tetraphosphonate, 1,4,7,10-tetraazacyclododecane-1,4,7,10- tetraaminomethylenephosphonate (DOTMP) has been labeled with 175YbCl3. Production, quality control and biodistribution studies of 175Yb-DOTMP were targeted in this study. 175Yb chloride with mean specific activity of 31 mCi/mg was obtained by thermal neutron flux (3×1013 n.cm-2.s-1) of a natural Yb2O3 sample (isotopic purity of 31.8% for 174Yb) in the Tehran Research Reactor (TRR). Radiolabeling was completed in one h by the addition of DOTMP at room temperature. The radiochemical purity was determined using ITLC and it was more than 98%. The results of biodistribution animal studies are excellent. It was rapidly taken up in the bone in 2 h after injection (ID/g%=3.92) and reminded after 4 d (ID/g%=3.91).